Enhancing Elementary Students’ Understanding of the Solar System through Smart TV and Solar Scope Integration: A Classroom Action Research Study - Ibermarza Ibermarza; Yurnalisma Dewi; Fitria Carli Wiseza; Ayu Wandari (Indonesian Technology and Education Journal, 2026)
This study was motivated by students’ low conceptual understanding and learning outcomes in the Solar System topic within Integrated Science and Social Studies (IPAS) learning at SDN 101 Bungo. The predominance of conventional teaching methods and the limited use of interactive media made it difficult for students to comprehend abstract scientific concepts. Therefore, this study aimed to improve students’ learning outcomes and classroom engagement through the implementation of Smart TV-based learning media integrated with the Solar Scope system. This research employed a Classroom Action Research design based on the Kemmis and McTaggart model, which consisted of two cycles involving planning, action, observation, and reflection. The participants were 25 sixth-grade students. Data were collected through achievement tests, classroom observations, and documentation and were analyzed using both quantitative and qualitative approaches. The findings revealed a substantial improvement in students’ academic achievement and learning activities. The average score increased from 65 in the pre-action stage to 70 in Cycle I and reached 85 in Cycle II. Similarly, the percentage of students achieving learning mastery improved from 52% to 60% and finally to 92%. Students also demonstrated higher levels of participation, interaction, collaboration, and motivation during the learning process. These findings indicate that the integration of Smart TV and Solar Scope provides meaningful visual experiences that facilitate students’ understanding of abstract concepts and promote more student-centered learning. Consequently, this instructional innovation can serve as an effective alternative for enhancing elementary science education in the digital era.